2012
DOI: 10.1111/j.1365-2184.2012.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of male germ cells from induced pluripotent stem cells in vitro and in reconstituted seminiferous tubules

Abstract: Our results suggest that iPS cells are able to differentiate into male germ cells in vitro and that reconstituted seminiferous tubules may provide a functional niche for exogenous iPS cell-derived male germ cells. Derivation of male germ cells from iPS cells has potential application for treating male infertility and provides an ideal platform for elucidating molecular mechanisms of male germ-cell development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 40 publications
2
54
0
Order By: Relevance
“…MVH is a specific marker for germ cells from the late migration stage to the postmeiotic stage and it plays an essential role in germ cell specification, proliferation and maintenance [Tanaka et al, 2000;Tilgner et al, 2010;Tian et al, 2011;Yang et al, 2012]. Using immunohistochemical analysis, Western blots and real-time PCR, we observed that MVH was expressed at higher levels in regenerated tubules from VEGF-treated grafts compared to SU5416-treated grafts, suggesting that VEGF/VEGFR 2 signaling plays an important role in testicular regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MVH is a specific marker for germ cells from the late migration stage to the postmeiotic stage and it plays an essential role in germ cell specification, proliferation and maintenance [Tanaka et al, 2000;Tilgner et al, 2010;Tian et al, 2011;Yang et al, 2012]. Using immunohistochemical analysis, Western blots and real-time PCR, we observed that MVH was expressed at higher levels in regenerated tubules from VEGF-treated grafts compared to SU5416-treated grafts, suggesting that VEGF/VEGFR 2 signaling plays an important role in testicular regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…MVH (also known as VASA) is a specific germ cell marker expressed in the cytoplasm of germ cells from spermatogonia to spermatids [Tian et al, 2011;Yang et al, 2012]. Immunohistochemistry revealed that MVH was expressed in the regenerated tubules of all groups, suggesting that male germ cells reside in the tubules and undergo proliferation and differentiation ( fig.…”
Section: Mvh Expression Analysis Of Regenerated Seminiferous Testis Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, there are two methods to produce male gametes from the pluripotent stem cells in vitro [20]: the monolayer differentiation and the embryoid body (EB) formation [24, 44]. Direct differentiation on monolayers of human fibroblast ensures more consistent differentiation results compared with EB formation [20].…”
Section: Stem Cells Are Novel and Unlimited Source For Male Gametementioning
confidence: 99%